The paradox of redistribution revisited: And that it may rest in peace? - Ive Marx; Lina Salanauskaite; Gerlinde Verbist (Luxembourg Income Study (LIS), 2013)
There is a long-standing controversy over the question of whether targeting social transfers towards the bottom part of the income distribution actually enhances or weakens their redistributive impact. Korpi and Palme have influentially claimed that 'the more we target benefits at the poor, the less likely we are to reduce poverty and inequality'. The basic empirical underpinning of this claim is a strong inverse relationship at the country level between social transfer targeting and redistributive impact. We show that this no longer holds as a robust empirical generalisation. The relationship between the extent of targeting and redistributive impact over a broad set of empirical specifications, country selections and data sources has in fact become a very weak one. For what it matters, targeting tends to be associated with higher levels of redistribution, especially when overall effort in terms of spending is high. We try to make substantive sense of this breakdown of the originally established relationship by focusing on two questions: first, what has changed in the countries originally included in the study and, second, what is different about the countries now additionally included in the analysis?
Keywords: 330